2016
DOI: 10.1016/j.juro.2016.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Prostate Imaging Reporting and Data System Version 2 for Prostate Cancer Detection

Abstract: A PI-RADS score of 5 had the highest prospective cancer detection rate (78%). A PI-RADS score of 4 had only a 30% cancer detection rate, which is lower than expected. Surprisingly, no or few significant cancers were detected at a PI-RADS score of 3 (16%). These early prospective data suggest that current criteria result in a high false-positive rate that lowers the cancer detection rate. Therefore, stricter criteria may be needed in the future to decrease false-positives and increase the cancer detection rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 12 publications
8
62
1
2
Order By: Relevance
“…The latest (153 patients and 287 lesions) series published by Kesch et al 2016 [20] using the same technique as we did shows similar detection rate of 34.8% and 29.9% for any and significant cancer, respectively. Another series (62 patients and 116 lesions) by Mertan et al 2016 [21] and Cash et al 2016 [22] (408 patients) reported similar results as well. The latest data including ours underline the poor performance of the PI-RADS scoring systems on a lesion based analysis.…”
Section: Discussionsupporting
confidence: 53%
“…The latest (153 patients and 287 lesions) series published by Kesch et al 2016 [20] using the same technique as we did shows similar detection rate of 34.8% and 29.9% for any and significant cancer, respectively. Another series (62 patients and 116 lesions) by Mertan et al 2016 [21] and Cash et al 2016 [22] (408 patients) reported similar results as well. The latest data including ours underline the poor performance of the PI-RADS scoring systems on a lesion based analysis.…”
Section: Discussionsupporting
confidence: 53%
“…Quentin et al showed a 9.4% increase in clinically significant cancer from transrectal US-guided biopsy to combined transrectal US-guided and in-bore MR-guided biopsy. In our population, 18 of 49 patients (36.7%) with prior (22,23). A diagnostic yield of 16%-26% for category 3 underscores the need consider category 3 and higher as the threshold for proceeding to biopsy, rather than using category 4 as the threshold.…”
Section: Genitourinary Imaging: In-bore 3-t Mr-guided Transrectal Tarmentioning
confidence: 78%
“…To address this, in early 2015, Prostate Imaging Reporting and Data System (v.2) guidelines were established by the American College of Radiology and the European Society of Urogenital Radiology [109] that aim to standardize all aspects of mpMRI. Initial prospective studies have revealed promising findings on its use in improving prostate adenocarcinoma care [110] and its impact on inter-observer agreement and related cancer detection [111, 112]. A multi-reader study with 34 patients revealed average sensitivity values of 91% and 63% for detecting index and all lesions across all readers, respectively.…”
Section: Prostate Adenocarcinomamentioning
confidence: 99%